SOCIALIZATION AND INSPECTION OF REFILL DRINKING WATER DEPOTS IN THE WORK AREA OF THE RAPAK MAHANG HEALTH CENTER - Kurniawan, Deny; Melinda, Lia; Pramaningsih, Vita (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2022)
Water is a chemical compound that is very important for the life of living things on this earth. The function of water for life cannot be replaced by other compounds. The main use of water and very vital for life is as drinking water. This is to meet the needs of water in the body. The refill drinking water depot is an example of processing water into drinking water and selling it directly to buyers. The existence of refill drinking water depots continues to increase in line with the dynamics of the community's need for quality and safe drinking water for consumption. Even though it is cheaper, not all this depots are guaranteed the safety of their products. This happens because of the weak supervision of the relevant agencies. Based on this, it is necessary to conduct socialization and inspections related to the Depot, especially in Tenggarong District within the working area of ??the Rapak Mahang Health Center. This activity was carried out with the aim of ensuring the quality of drinking water safety and increasing the knowledge of water depot refills owners regarding the hygiene sanitation of the refill drinking water depot in accordance with the established quality standards. This activity was carried out in several stages, ranging from interviews, the examinations, to the socialization stage. The process of this activity went quite well, as evidenced by the willingness of the owner during the socialization and inspection.